KONTRIBUSI IMAM AHMAD BIN HANBAL (164-241 H) DALAM PENGEMBANGAN METODOLOGI KRITIK HADIS: ANALISIS SANAD, MATAN, DAN PENGARUHNYA TERHADAP TRADISI KEILMUAN SUNNI - Isnan Ansory; Rheina Musakinah; Rasyiqah Rahmadewi (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
Prophetic hadith occupies a fundamental position as the second primary source of Islamic teachings after the Qur’an, making the preservation of its authenticity an essential scholarly endeavor. In the historical development of hadith criticism, Imam A?mad ibn ?anbal (164–241 AH) holds a pivotal role as one of the key figures in laying the foundations of naqd al-?ad?th. This study aims to examine Imam Ahmad’s contribution to the methodology of sanad and matn criticism and to analyze the influence of his approach on subsequent generations of scholars. Employing a qualitative descriptive method with a library research approach, this study draws upon primary sources such as Imam Ahmad’s works—particularly al-Musnad—and classical hadith literature, alongside secondary sources from modern academic studies. The findings reveal that Imam Ahmad applied an integrative methodology of hadith criticism, combining rigorous scrutiny of transmission chains with careful evaluation of textual content. His strict assessment of narrators, emphasis on the continuity of transmission, and rejection of matn that contradicts the Qur’an, mutaw?tir Sunnah, or established principles of Islamic law demonstrate the maturity of early hadith criticism. Imam Ahmad’s methodology significantly influenced later hadith scholars, including the compilers of the Kutub al-Sittah, the development of al-jar? wa al-ta‘d?l, the formation of the Hanbali school of law, and Sunni theological tradition. Thus, Imam Ahmad can be regarded as a transitional figure who played a crucial role in shaping the standards of hadith authenticity within classical Islamic scholarship.